CORRELATION ANALYSIS OF MUTUAL CHECK (MC), WORK DRAWINGS AND HUMAN RESOURCES ON THE PROGRESS OF CONSTRUCTION WORK - Nurjanah; Prima, Hangga; Salsabil, Ahmad Amru (Universitas Islam Balitar Blitar, 2024)
The Bendo Krosok River is part of the Brantas watershed system covering an area of 568 km2. This river originates on the slopes of Mount Willis, Mojo District, Kediri Regency, which empties into the Brantas River in Prambon District, Nganjuk Regency. Most of the cliff retaining walls in Maron Village sub -district experience landslides of 30 meters with a wall height of 5 meters, the distance between the wall and the road shoulder is 3 meters and there are electricity poles and telephone poles 1 meter away from the cliff retaining wall that landslides. The condition of the subgrade plays a very important role in determining the stability of the cliff retaining wall structure, especially near the planned highway. Poor soil conditions (soft soil) from former landfill and the quality of work/subgrade materials are the main causes of damage to cliff retaining walls which are caused by shifting, overturning and subsidence of the subgrade and subgrade soil. Natural factors also influence changes in the planned level of strength of the original soil's bearing capacity. To produce ideal cliff retaining wall construction, the wall stability planning needs to be reviewed and the safety factors against sliding, overtuning and decline must be sufficient and The soil pressure that occurs in the foundation soil must not exceed the permitted bearing capacity. The design of the cliff retaining wall structure is planned to be safe against shifting, overturning and collapse of the soil's bearing capacity. The dimensions of the new river bank retaining wall and the author are larger than the dimensions of the old wall and the soil bearing capacity value SPT 10 - 30 is obtained at a depth of 4.00 - 20.00 m, which includes Slightly Dense / Firm - Very Stiff Soil and walls This cliff barrier cannot be designed with a shallow foundation, there are no piles so it experiences sliding and overturning but must be designed with a deep foundation and the addition of piles as reinforcement. The results of stability calculations for both shear and overturning on the retaining walls of the Bendo Krosok river cliffs for